Variasi Bahasa dalam Tuturan Penjual dan Pembeli di Pasar Dupa Jalan Merpati Tangkerang Tengah Kecamatan Marpoyan Damai Kota Pekanbaru - Putri, Melinda Antoni; Erni (UIR PRESS, 2021)
In everyday life as social beings, humans use variety of variations to express something in the process of interacting with society both formally and informally. Language variation is caused by the existence of social interaction activities carried out by a very diverse community or group. The diversity of these languages ​​will increase if the language is used by a very large number of speakers and in a very wide area. This study examines language variations in the speech of sellers and buyers in the Dupa market, Jalan Merpati Tangkerang Tengah, Marpoyan Damai District, Pekanbaru City with the problem (1) what are the language variations in the speech of sellers and buyers in the incense market, Jalan Merpati Tangkerang Tengah, Marpoyan Damai Kota District. Pekanbaru, and (2) what are the functions of language variation in the speech of sellers and buyers at the Incense market on Merpati Tangkerang Tengah street, Marpoyan Damai District, Pekanbaru City. The theories used in this study are Abdul Chaer and Leonie Agustina (2010), and Alwasilah A. Chaedar (1993). While the method used is content analysis with a research approach that is a qualitative approach. Based on the results of this study, there are (1) language variations in the speech of sellers and buyers in the Dupa market Jalan Merpati Tangkerang Tengah, Marpoyan Damai District, which the researchers found with details of language variations in terms of speakers, namely dialects and chronicles, language variations in terms of usage, language variations. In terms of formality, there are familiar and relaxed varieties, and language variations in terms of facilities, namely variations in spoken language, and (2) the function of language variations in the speech of sellers and buyers at the Incense market, Jalan Merpati Tangkerang Tengah, Marpoyan Damai District, Pekanbaru City, with details of the instrumental function, the regulatory function, the personal function, the interactional function, the representational function, and the heuristic function. Where as what the researchers did not find were imaginative functions.